Material tinkering for design education on waste upcycling - Santulli, Carlo; Rognoli, Valentina (Design and Technology Education: An International Journal, 2020)
Materials are primary elements in the process of design and are gaining more and more attention in design education. The present work illustrates the practice of material tinkering, concentrating on its effects on design education, as regards the upcycling of waste into material demonstrators, deemed to assess their possibility to evolve into sustainable artefacts. After a general illustration of the scope and objectives of material tinkering, the exposition describes the recent experiences of this practice into design schools, highlighting its pedagogical significance worldwide, and in the particular case of the Italian situation. Finally, the exposition concentrates on the specific case of work carried out in two prestigious Italian Universities (Università di Camerino and Politecnico di Milano) from 2015. The paper tries to clarify its position and significance concerning previous literature, for what appears relevant to the education of designers and for their formation in the local context to be applicable worldwide. The research method evolves from trial-and-error, typical of experimentation on materials, to the conception of material demonstrators and suitability to be applied into products, having as boundaries the choice to use some kinds of waste in an upcycling philosophy.